Carbon quantum dot fluorescent material synthesized through efficient catalysis of cuprous oxide and preparation method of carbon quantum dot fluorescent material

By using cuprous oxide to catalyze the dehydration reaction of isopropanol and organic amine under the action of a catalyst, the synthesis temperature and time of carbon quantum dots were successfully reduced, and the problems of high reaction temperature and long time in the prior art were solved, and the preparation of efficient and green carbon quantum dot fluorescent materials were achieved.

CN119569038APending Publication Date: 2025-03-07SHANGHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411641740.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing hydrothermal/solvent thermal methods have high reaction temperatures and long time, resulting in high synthesis costs and low efficiency, making it difficult to meet the wide demand for carbon quantum dot fluorescent materials in biological applications.

Method used

Using cuprous oxide as a catalyst, carbon quantum dot fluorescent materials are synthesized under lower temperature and time conditions through the dehydration reaction of isopropanol and organic amine. The method includes adding glucose as a reducing agent under electromagnetic stirring conditions, forming a Cu2O colloidal catalyst, and reacting in a polytetrafluoroethylene reactor.

Benefits of technology

It greatly reduces the synthesis temperature and time of carbon quantum dots, realizes the efficient and green and environmentally friendly preparation of carbon quantum dot fluorescent materials of various colors, reduces the synthesis cost, and improves the quantum efficiency of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569038A_ABST
    Figure CN119569038A_ABST
Patent Text Reader

Abstract

The invention relates to a carbon quantum dot fluorescent material synthesized by efficient catalysis of cuprous oxide and a preparation method of the carbon quantum dot fluorescent material, and provides a synthesis method for preparing a bright carbon quantum dot fluorescent material by efficient catalysis of a dehydration decomposition reaction of isopropanol and organic amine by taking a Cu2O colloidal solution simultaneously synthesized by a one-step method as a catalyst. Copper salts such as copper chloride and copper acetate are used as starting raw materials of catalysts, isopropanol is used as a carbon source and a solvent, and organic amines such as ethylenediamine, o-phenylenediamine and 2, 3-diaminonaphthalene are used as nitrogen sources and organic alkali. Cu < 2 + > is hydrolyzed into a Cu (OH) 2 colloidal solution under the action of organic alkali; the Cu (OH) 2 colloidal solution is reduced into a Cu2O colloidal solution by glucose at a certain temperature; the Cu2O colloidal solution efficiently catalyzes the dehydration decomposition reaction of isopropanol and organic amine to synthesize the bright fluorescent carbon quantum dot material. According to the synthesis method, the reaction temperature and time for synthesizing the carbon quantum dots by a solvothermal method are greatly reduced. The method provided by the invention is an efficient, green and environment-friendly preparation method for synthesizing carbon quantum dot fluorescent materials with various colors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a cuprous oxide-efficient catalytic synthesis of a carbon quantum dot fluorescent material and a preparation method thereof, and belongs to the application field of fluorescent quantum dots. Background Art

[0002] Carbon quantum dots are mainly composed of carbon atoms and are nanoparticles with a particle size of less than 10nm. Carbon quantum dots have good biocompatibility, and the raw materials for synthesis include organic small molecules, biomass materials, etc. By incorporating electron-rich elements such as nitrogen (N) and sulfur (S), the luminescence efficiency of carbon quantum dots can be improved, the fluorescence color of carbon quantum dots can be regulated, and the synthesis of carbon quantum dot fluorescent materials with multiple fluorescent colors and high efficiency can be achieved. Carbon quantum dot fluorescent materials have a wide range of application value in biological fluorescence imaging, luminescent labeling of biological molecules, and fluorescent probes of biological molecules.

[0003] There are many methods for synthesizing carbon quantum dot fluorescent materials. Among them, the bottom-up hydrothermal and solvent thermal synthesis methods using organic small molecules or biomass materials as raw materials can adjust the morphology and degree of graphitization of carbon quantum dots by changing the reaction conditions (precursor, temperature, time, solvent). By adjusting the doping content of electron-rich atoms such as N and the modification of functional groups on the surface of carbon quantum dot particles, the energy level of the surface defect energy level of carbon quantum dots can be adjusted to achieve high efficiency, multiple colors, relatively uniform particle size distribution, and good dispersion in solvents. The synthesis of carbon quantum dots. Therefore, the hydrothermal / solvothermal synthesis method has become the most commonly used method for synthesizing carbon quantum dot fluorescent materials.

[0004] However, the chemical reaction of preparing carbon quantum dots by hydrothermal / solvothermal method is complicated, and the reaction temperature is usually higher than 180℃ and the reaction time is longer than 12 hours. Therefore, developing a green synthesis method of fluorescent carbon quantum dots with high efficiency and environmental protection under the action of catalyst to reduce the synthesis temperature and synthesis time of hydrothermal / solvothermal method can reduce the synthesis cost of carbon quantum and has practical value for the wide application of carbon quantum dot fluorescent materials. Summary of the invention

[0005] The purpose of the present invention is to reduce the synthesis temperature and synthesis time of carbon quantum dots synthesized by hydrothermal / solvothermal method, and to synthesize a high-efficiency, green and environmentally friendly preparation method of carbon quantum dot fluorescent materials with various colors. To achieve this purpose, isopropanol is used as a carbon source and solvent, and organic amines such as ethylenediamine, o-phenylenediamine, 2,3-diaminonaphthalene are used as nitrogen sources and organic bases. Copper salts such as copper chloride and copper acetate are used as raw materials for catalysts. Under the action of organic bases, Cu 2+Hydrolyze into Cu(OH)2 colloidal solution. Under certain temperature conditions, with glucose as a reducing agent, the cuprous oxide generated simultaneously in this complex reaction system can efficiently catalyze the dehydration reaction of isopropanol and organic amines to generate bright fluorescent carbon quantum dot fluorescent materials. By adding organic amines of different structures, the structure of the functional groups on the surface of carbon quantum dot particles is changed, and the surface defect energy level of carbon quantum dots is regulated to achieve the synthesis of carbon quantum dot fluorescent materials with various colors.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme:

[0007] The first object of the present invention is to provide a method for preparing a carbon quantum dot fluorescent material that is efficiently catalyzed by cuprous oxide. The method is a method for preparing a carbon quantum dot fluorescent material that uses cuprous oxide as a catalyst to efficiently catalyze the dehydration reaction of isopropanol and organic amines to synthesize brightly fluorescent carbon quantum dot fluorescent materials.

[0008] Further, the following steps are included:

[0009] a. Dissolve a certain amount of copper salt in isopropanol to obtain solution 1. Dissolve a certain amount of organic amine in isopropanol to obtain solution 2. Slowly add solution 2 to solution 1 under electromagnetic stirring, and adjust the pH of the mixed solution to 6-7. Then react for 10-30 minutes under 50-60℃ water bath temperature control to obtain a blue Cu(OH)2 colloidal solution, and use a red laser pen to detect the formation of Cu(OH)2 colloidal solution.

[0010] b. Dissolve a certain amount of glucose (as a reducing agent) in isopropanol and a small amount of water, add it to the above-mentioned Cu(OH)2 colloidal solution in batches under electromagnetic stirring, and continue the reaction for 10 to 60 minutes under 50-60°C water bath temperature control conditions. Red Cu2O colloid is gradually generated in the mixed solution, and the generation of Cu2O colloidal solution is detected with a red laser pen.

[0011] c. The mixed solution is transferred into a polytetrafluoroethylene reactor and reacted at 110-180°C for 0-4 hours (when the reaction time is 0, step c is not performed, and the carbon quantum dot fluorescent material can still be synthesized).

[0012] d. Cool naturally to room temperature, centrifuge for 5 to 10 minutes at 8000 to 10000 rpm to remove the generated cuprous oxide. Then dialyze with a 3500Da dialysis bag for 24 hours, the dialysate is isopropanol, remove the small molecule precursor substances, and obtain the carbon quantum dot fluorescent material. Furthermore, the copper salt can be one or more of hydrated copper acetate (Cu(CH3COO)2·H2O), copper acetate (Cu(CH3COO)2), copper chloride (CuCl2) or dihydrated copper chloride (CuCl2·2H2O).

[0013] Furthermore, the organic amine may be one or more of ethylenediamine, o-phenylenediamine, 2,3-diaminonaphthalene, and the like.

[0014] Optionally, the purified carbon quantum dot fluorescent material solution is rotary evaporated to remove the isopropanol solvent, and the solid is ultrasonically dispersed again in tetrahydrofuran or other solvents to obtain carbon quantum dot fluorescent materials of other colors by utilizing the solvent effect of the functional groups on the surface of the carbon quantum dots.

[0015] Furthermore, the luminescent color of the carbon quantum dot fluorescent material may be blue light, yellow light, green light or the like.

[0016] Compared with the prior art, the present invention has the following advantages:

[0017] 1) The present invention develops a green synthesis method for fluorescent carbon quantum dots that reduces the synthesis temperature and synthesis time of the solvent thermal method under the action of a catalyst, develops an efficient and environmentally friendly green synthesis method, can reduce the synthesis cost of carbon quanta, and has practical value for the wide practical application of carbon quantum dot fluorescent materials.

[0018] 2) The synthesis method of the present invention greatly reduces the reaction temperature and time of the solvothermal method for synthesizing carbon quantum dots. The preparation method provided by the present invention is an efficient, green and environmentally friendly preparation method for synthesizing carbon quantum dot fluorescent materials of various colors.

[0019] 3) The present invention uses Cu2O colloid as a catalyst, which greatly reduces the reaction temperature and synthesis time. The luminescent color of carbon quantum dots can be adjusted by using organic amines of different structures as starting materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the XRD pattern of the Cu2O nanoparticles synthesized simultaneously in Example 1.

[0021] Figure 2 (a, b, c) are transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM) and particle size distribution statistics of the blue CQD-1 synthesized in Example 1, respectively. Figure 2 The inset in (b) is the lattice fringes of its enlarged area.

[0022] Figure 3 (a, b) are the fluorescence excitation spectrum and emission spectrum of the isopropanol solution of the blue light CQD-1 synthesized in Example 1, respectively. Figure 3 The inset in (b) is a photograph of the sample under 365 nm ultraviolet light.

[0023] Figure 4 (a, b, c) are TEM images, HRTEM images and particle size distribution statistics of the green CQD-2-THF synthesized in Example 2, respectively. Figure 4 The inset in (b) is the lattice fringes of its enlarged area.

[0024] Figure 5 (a, b) are the fluorescence excitation spectrum and emission spectrum of the green CQD-2-THF synthesized in Example 2, respectively. Figure 5 The inset in (b) is a photograph of the sample under 365 nm UV light.

[0025] Figure 6 (a, b, c) are TEM images, HRTEM images and particle size distribution statistics of the yellow CQD-2-IPA synthesized in Example 2, respectively. Figure 6 The inset in (b) is the lattice fringes of its enlarged area.

[0026] Figure 7 This is the fluorescence emission spectrum of the yellow light CQD-2-IPA synthesized in Example 2, and the inset is a photo of it under 365nm ultraviolet light.

[0027] Figure 8 This is the fluorescence excitation spectrum of the yellow light CQD-2-IPA synthesized in Example 2.

[0028] Fig. 9 (a, b, c) are TEM images, HRTEM images and particle size distribution statistics of the yellow CQD-3 synthesized in Example 3, respectively. Fig. 9 The inset in (b) is the lattice fringes of its enlarged area.

[0029] Fig.10 (a, b) are the fluorescence excitation spectrum and emission spectrum of the isopropanol solution of the yellow light CQD-3 synthesized in Example 3, respectively. Fig.10 The inset in (b) is a photograph of the sample under 365 nm ultraviolet light.

[0030] In order to reduce the synthesis temperature and synthesis time of carbon quantum dots, the present invention designs to use a Cu2O colloidal solution synthesized in one step as a catalyst. In order to control the luminescence color of carbon quantum dots, the present invention designs to use different organic amine precursors to control the energy level of defect energy levels on the surface of carbon quantum particles to control the luminescence color of carbon quantum dots, and to use different solvent molecules to control the surface energy level of carbon quantum dots through the intermolecular interaction between the functional groups on the surface of carbon quantum dot particles to control their luminescence color. The designed synthesis path is as follows.

[0031] Synthetic route 1:

[0032]

[0033] In the above formula, C6H 12 O6 is glucose, THF is tetrahydrofuran, and IPA is isopropanol. DETAILED DESCRIPTION

[0034] The following is a detailed description of an embodiment of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.

[0035] The present invention provides a method for preparing a bright carbon quantum dot fluorescent material by using a Cu2O colloidal solution synthesized in one step as a catalyst to efficiently catalyze the dehydration and decomposition reaction of isopropanol and organic amine. The present invention uses copper salts such as copper chloride and copper acetate as the starting raw materials of the catalyst, isopropanol as the carbon source and solvent, and organic amines such as ethylenediamine, o-phenylenediamine, and 2,3-diaminonaphthalene as the nitrogen source and organic base. 2+ Under the action of organic base, it is hydrolyzed into Cu(OH)2 colloidal solution. Cu(OH)2 colloidal solution is reduced to Cu2O colloidal solution by glucose at a certain temperature. Cu2O colloidal solution efficiently catalyzes the dehydration decomposition reaction of isopropanol and organic amine to synthesize bright fluorescent carbon quantum dot materials. This synthesis method greatly reduces the reaction temperature and time of the solvent thermal method for synthesizing carbon quantum dots. For example, the optimal synthesis temperature of yellow light carbon quantum dots (CQD-2-IPA, with an absolute quantum efficiency of 26.6%) is 60°C, and the optimal synthesis time is 10 minutes. The preparation method provided by the present invention is an efficient, green and environmentally friendly preparation method for synthesizing carbon quantum dot fluorescent materials of various colors.

[0036] The present invention is described in detail below in conjunction with specific embodiments, but is by no means intended to limit the present invention. Features such as preparation methods, materials, structures or composition ratios not explicitly described in this technical solution are considered to be common technical features disclosed in the prior art.

[0037] The following examples will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several modifications and improvements may be made without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0038] The practice of the present invention may employ conventional techniques of chemistry within the skill of the art. In the following examples, efforts have been made to ensure accuracy with respect to numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be accounted for.

[0039] The above scheme is further described below in conjunction with specific implementation examples. In the following implementation examples, the chemical substances used can be purchased commercially without further purification.

[0040] Example 1: Synthesis of blue light carbon quantum dots (CQD-1)

[0041] a. Dissolve 170.5 mg (1 mmol) of cupric chloride dihydrate in 5 mL of isopropanol to obtain solution 1. Ultrasonic disperse 60 mg of ethylenediamine (1 mmol) in 5 mL of isopropanol to obtain solution 2. Slowly add solution 2 to solution 1 under electromagnetic stirring, and the pH of the mixed solution is 6 to 7. Then react for 10 to 30 minutes under 60°C water bath temperature control to obtain a blue Cu(OH)2 colloidal solution, and use a red laser pen to detect the formation of the colloidal solution.

[0042] b. Add 90 mg of glucose (0.5 mmol) to 20 mL of isopropanol, add a few drops of water in a 60°C water bath with electromagnetic stirring until the glucose is dissolved, and then add it to the mixed solution containing the Cu(OH)2 colloid in batches. Continue the reaction for 60 minutes in a 60°C water bath to obtain a mixed solution containing red Cu2O colloid, and use a red laser pen to detect the formation of the Cu2O colloid solution.

[0043] c. The mixed solution containing the Cu2O colloid was transferred into a polytetrafluoroethylene autoclave and reacted at 160°C for 2 hours. The mixture was cooled to room temperature naturally and centrifuged at 8000 rpm for 10 minutes to remove the generated cuprous oxide (Cu2O). The mixture was then dialyzed for 24 hours using a 3500Da dialysis bag with isopropanol as the dialysis fluid. The isopropanol dialysis fluid was replaced every 12 hours to remove the small molecule precursor substances, thereby obtaining the blue light carbon quantum dot fluorescent material (CQD-1).

[0044] Attached Figure 1 This is the XRD pattern of the Cu2O nanoparticles synthesized simultaneously in Example 1. It is cubic Cu2O. The average particle size of the cubic Cu2O nanoparticles calculated by Scherrer formula (1-1) is about 25.3 nm.

[0045]

[0046] Where λ is the wavelength of X-ray, λ = 0.154056nm, β is the half-peak width of the main diffraction peak converted into radians, β = 5.41×10 -3 , θ is the angle of the main diffraction peak, θ = 18.2°, and D is the average particle size.

[0047] Attached Figure 2 The transmission electron microscopy (TEM) image, high-resolution transmission electron microscopy (HRTEM) image and particle size distribution statistics of the blue CQD-1 synthesized in Example 1 are given. Figure 2The inset in (b) is the lattice fringes of the magnified area. The CQD-1 particles are spherical, uniformly dispersed, and have an average particle size of 2.2 nm. The inset is the lattice diffraction fringes of CQD-1 quantum dots, whose interplanar spacing d = 0.21 nm corresponds to the

[100] interplanar spacing of graphite C, proving the successful synthesis of CQD-1 quantum dots.

[0048] Attached Figure 3 (a, b) are the fluorescence excitation spectrum and emission spectrum of the isopropanol solution of the blue light CQD-1 synthesized in Example 1, respectively. Figure 3 The inset in (b) is a photo of it under 365nm UV light. The maximum excitation wavelength of CQD-1 is 375nm, and the maximum emission wavelength is 444nm. Under 365nm UV light, CQD-1 emits bright blue fluorescence with an absolute quantum efficiency of 15.6%.

[0049] Example 2: Synthesis of yellow (CQD-2-IPA) and green (CQD-2-THF) carbon quantum dots.

[0050] a. Dissolve 200 mg of hydrated copper acetate (1 mmol) in 10 mL of isopropanol to obtain solution 1. Dissolve 108 mg of o-phenylenediamine (1 mmol) in 10 mL of isopropanol solution by ultrasonication to obtain solution 2. Slowly add solution 2 to solution 1 under electromagnetic stirring, and the pH of the mixed solution is 6-7. Then react for 10 minutes under 60°C water bath temperature control to obtain a blue Cu(OH)2 colloidal solution, and use a red laser pen to detect the formation of the colloidal solution.

[0051] b. Add 90 mg of glucose (0.5 mmol) to 10 mL of isopropanol. Add a few drops of water in a 60°C water bath with electromagnetic stirring until the glucose dissolves. Then add it to the mixed solution containing the above-mentioned Cu(OH)2 colloid in batches to gradually generate a red Cu2O colloid solution. Use a red laser pen to detect the generation of the Cu2O colloid solution. Continue the reaction for 10 minutes in a 60°C water bath. After the reaction, a brown suspension with bright yellow fluorescence is obtained, which is naturally cooled to room temperature.

[0052] c. Centrifuge for 10 minutes at 10,000 rpm to remove the generated cuprous oxide and larger carbon particles. Then dialyze for 24 hours using a 3,500Da dialysis bag with isopropanol as the dialysis fluid, replacing the isopropanol dialysis fluid every 12 hours to remove the small molecule precursor substances, thus obtaining the yellow light carbon quantum dot fluorescent material (CQD-2-IPA).

[0053] d. The 10 mL CQD-2-IPA solution purified by a 3500 Da dialysis bag was rotary evaporated to remove the isopropanol solvent. The solid was re-ultrasonicated and dispersed in 30 mL tetrahydrofuran, and the green light carbon quantum dots (CQD-2-THF) were obtained by utilizing the solvent effect of the functional groups on the surface of the carbon quantum dots.

[0054] Attached Figure 4 The TEM image, HRTEM image and particle size distribution statistics of the green CQD-2-THF synthesized in Example 2 are given. Figure 4 The inset in (b) is the lattice fringes of the magnified area. The CQD-2-THF particles are spherical, uniformly dispersed, and have an average particle size of 3.6 nm. The inset is the lattice diffraction fringes of CQD-2-THF quantum dots, whose interplanar spacing d = 0.21 nm corresponds to the

[100] interplanar spacing of graphite C, proving the successful synthesis of CQD-2-THF quantum dots.

[0055] Attached Figure 5 (a, b) are the fluorescence excitation spectrum and emission spectrum of the green light CQD-2-THF synthesized in Example 2, respectively. Figure 5 The inset in (b) is a photo of it under 365nm UV light. The maximum excitation wavelength of CQD-2-THF is 427nm, and the maximum emission wavelength is 516nm. Under 365nm UV light, CQD-2-THF emits bright green fluorescence with an absolute quantum efficiency of 20.7%.

[0056] Attached Figure 6 The TEM image, HRTEM image and particle size distribution statistics of the yellow light CQD-2-IPA synthesized in Example 2 are given. Figure 6 The inset in (b) is the lattice fringes of the magnified area. The CQD-2-IPA particles are spherical, uniformly dispersed, and have an average particle size of 4.1 nm. The inset is the lattice fringes of CQD-2-IPA quantum dots, whose interplanar spacing d = 0.21 nm corresponds to the

[100] interplanar spacing of graphite C, proving the successful synthesis of CQD-2-IPA quantum dots.

[0057] Attached Figure 7 This is the emission spectrum of the yellow CQD-2-IPA synthesized in Example 2, and the inset is a photo of it under 365nm ultraviolet light. The maximum emission wavelength of CQD-2-IPA is 540nm, and it emits bright yellow fluorescence under 365nm ultraviolet light, with an absolute quantum efficiency of 26.6%.

[0058] Attached Figure 8This is the fluorescence excitation spectrum of the yellow CQD-2-IPA synthesized in Example 2. The maximum excitation wavelength of CQD-2-IPA is 427nm, which is a wide excitation absorption band located in the 400-450nm region, which is about 1 times wider than the excitation absorption band of CQD-2-THF.

[0059] Example 3: Synthesis of yellow light carbon quantum dots (CQD-3)

[0060] a. Dissolve 60 mg of hydrated copper acetate (0.3 mmol) in 5 mL of isopropanol to obtain solution 1. Ultrasonic disperse 47.5 mg of 2,3-diaminonaphthalene (0.3 mmol) in 10 mL of isopropanol to obtain solution 2. Slowly add solution 2 to solution 1 under electromagnetic stirring, and the pH of the mixed solution is 6-7. Then react for 20 minutes under 60°C water bath temperature control to obtain a blue Cu(OH)2 colloidal solution.

[0061] b. Add 27 mg of glucose (0.15 mmol) to 15 mL of isopropanol, add a few drops of water in a 60°C water bath with electromagnetic stirring until the glucose is dissolved, and then add it to the above-mentioned mixed solution of Cu(OH)2 colloid in batches. Continue the reaction for 60 minutes in a 60°C water bath to obtain a mixed solution containing red Cu2O colloid.

[0062] c. The mixed solution containing the Cu2O colloid was transferred into a polytetrafluoroethylene autoclave and reacted at 180°C for 2 hours. The mixture was cooled to room temperature naturally and centrifuged at 10,000 rpm for 5 minutes to remove the generated cuprous oxide and larger carbon particles. The mixture was then dialyzed for 24 hours using a 3500Da dialysis bag with isopropanol as the dialysis fluid. The isopropanol dialysis fluid was replaced every 12 hours to remove the small molecule precursor substances, thereby obtaining the yellow carbon quantum dot fluorescent material (CQD-3).

[0063] Attached Fig. 9 The TEM image, HRTEM image and particle size distribution statistics of the yellow CQD-3 synthesized in Example 3 are given. Fig. 9 The inset in (b) is the lattice fringes of the magnified area. The CQD-3 particles are spherical, uniformly dispersed, and have an average particle size of 2.7 nm. The inset is the lattice fringes of CQD-3 quantum dots, whose interplanar spacing d = 0.21 nm corresponds to the

[100] interplanar spacing of graphite C, proving the successful synthesis of CQD-3 quantum dots.

[0064] Attached Fig.10 (a, b) are the fluorescence excitation spectrum and emission spectrum of the isopropanol solution of the yellow CQD-3 synthesized in Example 3, respectively. Fig.10The inset in (b) is a photo of it under 365nm UV light. The maximum excitation wavelength of CQD-3 is 373nm, and there is a broad and strong excitation absorption band in the visible region of 400nm to 450nm. The maximum emission wavelength of CQD-3 is 548nm, and it emits bright yellow fluorescence under 365nm UV light, with an absolute quantum efficiency of 16.9%.

[0065] In summary, the present invention has the following substantial advantages compared with the prior art:

[0066] 1. Using Cu2O colloid as a catalyst greatly reduces the reaction temperature and synthesis time. For example, the optimal reaction temperature of the synthesized yellow light carbon quantum dots (CQD-2-IPA) in Example 2 is 60°C, and the optimal reaction time is 10 minutes, and there is no need to react in a polytetrafluoroethylene reactor. In Example 1, the optimal reaction temperature of the synthesized blue light carbon quantum dots (CQD-1) is 160°C, and the optimal reaction time is 2 hours. In Example 3, the optimal reaction temperature of the synthesized yellow light carbon quantum dots (CQD-3) is 180°C, and the optimal reaction time is 2 hours.

[0067] 2. For Example 2, yellow carbon quantum dots with a quantum efficiency of 26.6% can be quickly prepared. The reaction takes only 10 minutes in a 60°C water bath, and high temperature and high pressure synthesis conditions are not required. The synthesis cost is greatly reduced, and it is a green and economical synthesis method.

[0068] 3. The present invention uses organic amines of different structures as starting materials to adjust the luminescent color of carbon quantum dots.

[0069] Foregoing content has been described in detail embodiments of the present invention in conjunction with the accompanying drawings, but the present invention is not limited to these specific embodiments. According to the synthetic method proposed by the present invention, multiple experimental schemes can be adjusted and changed. Any modification, improvement, substitution, combination or simplification carried out under the spirit, essence and principle framework of the technical scheme of the present invention are all considered as equivalent alternative means. As long as these changes meet the purpose of the present invention, and do not deviate from the technical principle and design of the present invention, they should be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon quantum dot fluorescent material by efficient catalysis of cuprous oxide, characterized in that: The preparation method uses cuprous oxide as a catalyst to catalyze the dehydration reaction of isopropanol and organic amine to synthesize a brightly fluorescent carbon quantum dot fluorescent material.

2. The method for preparing a carbon quantum dot fluorescent material by efficient catalysis of cuprous oxide according to claim 1, characterized in that The preparation method comprises the following steps: a. Dissolve a certain amount of copper salt in isopropanol to obtain solution 1, and dissolve a certain amount of organic amine in isopropanol to obtain solution 2. Slowly add solution 2 to solution 1 under electromagnetic stirring, adjust the pH of the mixed solution to 6-7, and then react for 10-30 minutes under a water bath temperature control condition of 50-60°C to obtain a blue Cu(OH)2 colloidal solution; b. Dissolve a certain amount of glucose in isopropanol and a small amount of water, add it to the above-mentioned Cu(OH)2 colloidal solution in batches under electromagnetic stirring, and continue to react for 10 to 60 minutes in a water bath at 50 to 60°C to obtain a red Cu2O colloidal mixed solution; c. The mixed solution was transferred into a polytetrafluoroethylene reactor and reacted at 110 to 180°C for 0 to 4 hours; d. Cool naturally to room temperature, centrifuge at 8000-10000 rpm for 5-10 minutes to remove the generated cuprous oxide particles, and then dialyze with a 3500Da dialysis bag for 24 hours with isopropanol as the dialysate to remove small molecule precursor substances, thereby obtaining the carbon quantum dot fluorescent material.

3. The method for preparing a carbon quantum dot fluorescent material by efficient catalysis of cuprous oxide according to claim 2, characterized in that: The copper salt is one or more of Cu(CH3COO)2·H2O, CuCl2·2H2O, Cu(CH3COO)2, and CuCl2; The organic amine is one or more of ethylenediamine, o-phenylenediamine and 2,3-diaminonaphthalene.

4. A highly efficient catalytic synthesis of carbon quantum dot fluorescent material by cuprous oxide prepared by the preparation method according to any one of claims 1 to 3.